Enhancing Physical Education, Sports, and Health for Elementary Students: Evidence from Elementary School Students 1 Ganti, East Praya - Ashari, Lalu Hasan; Zuhad, Fikri; Anshori, Muhammad (Lembaga Publikasi Ilmiah Nusantara, 2024)
The purpose of this study was to analyze the level of student learning processes in physical education, particularly in the 100-meter running activity, at Elementary School Students 1 Ganti Elementary School. This research employed a descriptive quantitative approach by utilizing data collection techniques such as observation, documentation, and test-based assessment, followed by data analysis. The research population consisted of 26 sixth-grade students who participated in the learning process. Learning achievement was measured using pre-test and post-test scores across different assessment categories. The results revealed that students demonstrated an improvement in learning outcomes. In the medium category, the pre-test score reached 71.4%, while the post-test increased to 80%. In the high KKM category, the pre-test score was 85%, and the post-test score rose to 87.28%. These findings indicate that the implementation of structured learning activities positively impacted student performance in the 100-meter running test. Overall, the study suggests that systematic evaluation and practice can enhance student achievement and engagement in physical education.